CD9 regulates proliferation, invasion, migration and radioresistance of esophageal squamous cell carcinoma by activating AKT/GSK3β signaling pathway - Hou, Liubing; Hao, Zengyao; Zhang, Ge; Li, Jiayuan; Wang, Yu; Xue, Xiaoying; Zhou, Huandi (Frontiers in Oncology, 2025)
BackgroundRadioresistance poses a major therapeutic challenge in ESCC, significantly impacting patient prognosis. CD9, as a crucial membrane regulatory protein, exhibits dual regulatory roles in various cancers, yet its precise mechanism in ESCC radioresistance remains unclear. This study aims to systematically elucidate the molecular mechanisms by which CD9 regulates malignant phenotypes and radiosensitivity through the AKT/GSK3β signaling pathway in ESCC.MethodsTCGA data, ESCC tissues microarray, in vitro experiments, and patient cohorts were utilized to investigate the expression patterns, functional mechanisms, and clinical relevance of CD9 in ESCC. CD9 was overexpressed in Eca109 cells (with low baseline expression) and knocked down in TE13 cells (with high endogenous expression). Functional assays, including proliferation, migration, invasion, and radioresistance tests, were conducted. Western blotting was used to explore the changes in key molecules of the AKT/GSK3β pathway. Survival analysis was performed on 82 ESCC cases from TCGA. Retrospectively collected radical radiotherapy specimens (n=14) from our institutional biobank underwent immunohistochemical quantification of CD9 expression correlated with survival outcomes.ResultsTCGA data analysis and 32 paired ESCC and adjacent non-tumorous tissues microarray revealed that CD9 expression was higher in ESCC tissues than in normal tissues, and was associated with tumor stage or lymph node metastasis. Functional validation demonstrated CD9 overexpression in Eca109 cells augmented proliferation, migration and invasion capacity, while enhancing radioresistance (SF2 increased from 0.488 to 0.596, SER decreasing to 0.888). Conversely, CD9 knockdown in TE13 cells reduced SF2 from 0.579 to 0.461, and SER up to 1.244. Mechanistically, CD9 modulated p-AKT (ser473) and p-Gsk3β (ser9) levels increased to 1.95-fold and 1.42-fold in overexpression models, respectively, with 58% and 33% reductions in knockdown group. TCGA cohort analysis (n=82) revealed no significant OS/DSS/PFI differences by CD9 expression (P>0.05). Intriguingly, radiotherapy subgroup analysis (n=29) suggested CD9-low patients exhibited a trend toward prolonged OS (P=0.067) DSS (P=0.067) and PFI (P=0.179). ROC demonstrated notable predictive capacity for 3-/5-year OS (AUC=0.681/0.851), DSS (AUC=0.651/0.778) and PFI (AUC=0.853/0.824).ConclusionsCD9 promotes ESCC progression and radioresistance by activating the AKT/GSK3β pathway and holds promise as a potential prognostic biomarker and therapeutic target for ESCC.